Peran Keluarga dalam Membina Akhlak Pada Anak Di MI Raudlatul Kholafiyah - Umami, Zaimatul (INNOVASI : JURNAL INOVASI PENDIDIKAN, 2025)
Moral education constitutes a fundamental aspect of character formation in children, with the primary role resting in the hands of the family before the child enters formal education. This study aims to identify the role of the family in fostering children’s moral development and its impact on character formation at MI Raudlatul Kholafiyah. Employing a qualitative approach with in-depth interviews and observations, the research involved parents and educators as participants. The findings indicate that families make a significant contribution to moral development through exemplary behavior, religious value education, and the enforcement of discipline, although challenges such as limited time and insufficient understanding of effective methods still persist. In conclusion, family-based moral guidance plays a crucial role in shaping children’s character, emphasizing the need for stronger collaboration between families and schools